2004
DOI: 10.1186/cc2859
|View full text |Cite
|
Sign up to set email alerts
|

Clinically important deep vein thrombosis in the intensive care unit: a survey of intensivists

Abstract: IntroductionOutside the intensive care unit (ICU), clinically important deep vein thrombosis (DVT) is usually defined as a symptomatic event that leads to objective radiologic confirmation and subsequent treatment. The objective of the present survey is to identify the patient factors and radiologic features of lower limb DVT that intensivists consider more or less likely to make a DVT clinically important in ICU patients.MethodsOur definition of clinically important DVT was a DVT likely to result in short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Observational studies have identified risk factors for DVT (4, 710) while our survey indicates factors considered important by practitioners. Other surveys have also reported patient factors and radiologic features that make VTE clinically significant (39, 42). Before conducting a randomized trial of thromboprophylaxis in children, it is essential to perform a prospective multicenter observational study to examine the burden of illness of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have identified risk factors for DVT (4, 710) while our survey indicates factors considered important by practitioners. Other surveys have also reported patient factors and radiologic features that make VTE clinically significant (39, 42). Before conducting a randomized trial of thromboprophylaxis in children, it is essential to perform a prospective multicenter observational study to examine the burden of illness of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, co-morbidity conditions added points to the risk score, resulting in the high-risk category. The analysis in this study focused on ICU versus non-ICU patients [1,9,[48][49][50][51][52] because specific guidelines for the ICU population are established [9,[53][54][55][56][57][58][59][60][61][62]. In the ICU group, two-thirds of the patients received appropriate prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically signifi cant VTE was defi ned as PE, proximal symptomatic or asymptomatic DVT, and symptomatic distal DVT. 9,14,15 Decisions on VTE treatment were left to the discretion of the patient's primary team.…”
Section: Compression Ultrasonographymentioning
confidence: 99%
“…Prior, well-conducted studies were performed in more heterogeneous groups of critically ill patients that included surgical patients. 1,[7][8][9][10] Sepsis is characterized by pathophysiologic processes distinct in many ways from patients in trauma, surgical, neurologic, and cardiology ICUs. Th is absence of data hinders assessments of the effectiveness of guideline-recommended VTE prophylaxis in severe sepsis and septic shock and limits advances in the prevention of VTE among these patients.…”
mentioning
confidence: 99%